Analisis Laporan Keuangan PT Medikaloka Hermina TBK - Hajnurisa Aini; Resa Sandia; Sri Retnaning Sampurnaningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the financial performance and profitability determinants of PT Medikaloka Hermina Tbk during the period 2020–2025 amid the aggressive expansion of Indonesia’s healthcare sector, which is relatively resilient to global economic fluctuations. The research employs a quantitative descriptive method using financial ratio analysis and panel data regression with a Random Effect Model, examining the effects of Current Ratio (CR), Total Assets Turnover (TATO), and Debt to Equity Ratio (DER) on Net Profit Margin (NPM). The descriptive results indicate relatively sound liquidity conditions, varying levels of asset utilization efficiency, and a leverage-oriented capital structure. Partial test results (t-test) reveal that CR, TATO, and DER do not individually have a significant effect on NPM; however, the simultaneous test (F-test) shows that these variables jointly have a significant influence on profitability. These findings suggest that corporate profitability is not driven by individual financial ratios alone, but rather by the combined interaction of liquidity, asset efficiency, and solvency, along with strategic factors such as hospital network expansion and the involvement of institutional investors. The results provide important insights for management and investors in assessing financial sustainability and long-term value creation in the healthcare industry.